2005
DOI: 10.1096/fj.04-2733fje
|View full text |Cite
|
Sign up to set email alerts
|

Electrical inhibition of lens epithelial cell proliferation: an additional factor in secondary cataract?

Abstract: Cataract is the most common cause of blindness but is at least curable by surgery. Unfortunately, many patients gradually develop the complication of posterior capsule opacification (PCO) or secondary cataract. This arises from stimulated cell growth within the lens capsule and can greatly impair vision. It is not fully understood why residual lens epithelial cell growth occurs after surgery. We propose and show that cataract surgery might remove an important inhibitory factor for lens cell growth, namely elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Both the cell cycle and the mitotic spindle are targets for physiological extracellular EFs Wang et al, 2005;Song et al, 2002), and regulating these might have a profound impact on the control of tumours. For example, cultured rat lens epithelial cells and bovine endothelial cells show markedly reduced proliferation rates in a physiological EF.…”
Section: Physiological DC Efsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the cell cycle and the mitotic spindle are targets for physiological extracellular EFs Wang et al, 2005;Song et al, 2002), and regulating these might have a profound impact on the control of tumours. For example, cultured rat lens epithelial cells and bovine endothelial cells show markedly reduced proliferation rates in a physiological EF.…”
Section: Physiological DC Efsmentioning
confidence: 99%
“…For example, cultured rat lens epithelial cells and bovine endothelial cells show markedly reduced proliferation rates in a physiological EF. The EF suppresses cyclin-E expression and increases expression of p27 kip1 (an inhibitor of the cyclin-E-Cdk2 complex), and consequently cells fail to make the G1-S-phase transition and undergo cell-cycle arrest Wang et al, 2005). In rat corneal epithelial cells in vivo, however, an endogenous EF enhanced proliferation and oriented the mitotic spindle (Song et al, 2002).…”
Section: Physiological DC Efsmentioning
confidence: 99%
“…They control cell migration (McCaig et al, 2009;Prevarskaya et al, 2010;Yao et al, 2008;Yasuda and Adams, 2010), proliferation (Blackiston et al, 2011) and differentiation (Sundelacruz et al, 2009) in a wide variety of systems. Although epithelial electric fields have been implicated in adult eye wound healing Wang et al, 2005;Zhao et al, 2006), the roles of ion flows in eye development have not been explored. In Xenopus laevis, we have uncovered an endogenous role for plasma membrane voltage gradients during eye development, and show that artificially induced changes in transmembrane potential (V mem ) are sufficient to induce well-formed eyes outside of the anterior neural field.…”
Section: Introductionmentioning
confidence: 99%
“…Such electric fields are generated when the epithelial layer is disrupted instantaneously and the lesion short-circuits the transepithelial potential difference (2)(3)(4)(5)(6)(7). Electric currents at wounds in human skin (4,(8)(9)(10)(11) and in rodent cornea and skin (5,7,(12)(13) have been measured with various techniques, such as vibrating probes, micro-glass electrodes, micro-needle arrays, and bioelectric imagers (5,12,(14)(15)(16). For example, it is reported that a large outward current of 4 mA cm -2 was measured at the wound edges of rat cornea and human skin.…”
Section: Introductionmentioning
confidence: 99%